Poetică și ornamentică - Laurențiu Hanganu (Revista de Istorie și Teorie Literară)
The study discusses the relationship between poetry and ornamentation in the light of Baudelaire’s theory of correspondences. Starting from the title of Edgar Poe’s volume, The Tales of the Grotesque and the Arabesque, Baudelaire notices that the two art motifs are an illustration of the dual nature of modern poetry, which is simultaneously harmonious and dissonant. At the same time, the poetic phrase has the sinuous course of the arabesque line, proving that poetry is a palimpsest of all artistic expression. The kinship of poetry and ornamentation, which transcends Lessing’s opposition between arts of time and arts of space, is the archetype of Baudelaire’s correspondences, which restores at the phantasy level a lost plenitude — a completeness still present in the form of the medieval manuscript.